The no-nonsense guides: essential practical approaches for the consultant forensic psychiatrist - Davoren, Mary (Seminars in forensic psychiatry, 2024)
This chapter is a guide to taking on a first consultant post in forensic psychiatry, a guide to supervising trainee doctors in forensic psychiatry and an overview of advice from a group of senior clinical directors in forensic psychiatry across multiple jurisdictions. It is designed to offer informal advice to consultant forensic psychiatrists on a wide range of issues that pertain to clinical practice and management that is rarely contained in textbooks.